Assessing the Temporal Variation in the Perceived Eects of Invasive Plant Species on Rural Livelihoods: A Case of Mikania micrantha Invasion in Nepal - Rai, Rajesh Kumar; Rai, Roshani (Conservation Science, 2013)
Aim This study aims to assess effects of invasion of Mikania micrantha on the livelihoods of rural communities and evaluates how perceived effects vary with the presence duration of invasive plants in a particular landscape. Location The study was conducted in the buffer zone communities of two protected areas in Nepal—Koshi Tappu Wildlife Reserve and Chitwan National Park. Materials and Methods Questionnaire interviews were performed among a total of 473 households from the target communities. The questionnaire mainly focused on a five-year gap evaluation of the current situation. The households were stratified into three strata based on their proximity to the forest and a systematic random sampling was used to select the households. Household heads of either gender were interviewed based on their availability during the visit. Key findings The results show that time decay effects exist in the interface between invasive plants and rural livelihoods, as people gradually start to consider that these plants have self-grown in their landscape. However, the number of affected households increases with duration of the stay of invasive plants in the landscape. Conservation implications The study shows that the perceived effects of invasive plants on rural households vary over time, and hence the response of rural households to the invasion. On the contrary, the perceived ecological effects of invasive plants remain the same. The results indicate the complication in managing the invaded area particularly in rural areas, which has forced the local people to use invasive plants such as Mikania in their daily lives in the absence of any strategy to control its spread. However, it can be concluded that Mikania cannot win the support of local communities in the invaded areas. DOI: http://dx.doi.org/10.3126/cs.v1i1.8579 Conservation Science 2013 1(1), 13-18